2010
DOI: 10.4103/0028-3886.66085
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of major neurological improvement after intravenous thrombolysis in acute ischemic stroke: A hospital-based study from south India

Abstract: Age <60 years, glucose levels <8 mmol/L and mild to moderate stroke severity (NIHSS median score 10+/-6) was associated with major neurological improvement after intravenous rt-PA. Major neurological improvement at 24 h after the administration of intravenous thrombolysis independently predicted good outcome at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
4
13
0
Order By: Relevance
“…Most studies that have examined early response to tPA focused on clinical findings 24 hours after stroke. 7 In clinical practice, however, decisions regarding additional therapies after stroke must be made within minutes to a few hours when additional neuroprotection or tissue salvage is still possible. 8 …”
Section: Discussionmentioning
confidence: 99%
“…Most studies that have examined early response to tPA focused on clinical findings 24 hours after stroke. 7 In clinical practice, however, decisions regarding additional therapies after stroke must be made within minutes to a few hours when additional neuroprotection or tissue salvage is still possible. 8 …”
Section: Discussionmentioning
confidence: 99%
“…A subset of patients treated with IV tPA have a significant recovery, shedding a substantial component of their neurological deficit within 24 hours [6][7][8][9][10][11][12]14]. This phenomenon has been documented in a number of studies, and has been labelled under a wide array of names including "rapid neurological recovery", "early neurological improvement", "major neurological improvement", "dramatic recovery" and the "Lazarus phenomenon".…”
Section: Rapid Neurological Recovery: Definitions Incidence and Outcomementioning
confidence: 99%
“…Despite the differing labels and definitions, the inci-dence and outcomes of rapid neurological recovery have been reported consistently across the literature. Studies showed that between 18% -33% of patients treated with IV tPA experienced some form of early recovery [6][7][8][9]11,12,14]. Furthermore, patients with rapid neurological recovery have lower 30 day mortality and are far more likely to have a favourable functional outcome (modified Rankin Score of 0 or 1) at 3months than patients without early recovery [6][7][8][9][10]14].…”
Section: Rapid Neurological Recovery: Definitions Incidence and Outcomementioning
confidence: 99%
See 2 more Smart Citations